2021
DOI: 10.1186/s12902-021-00717-6
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, even newly defined by HbA1c testing, is associated with an increased risk of in-hospital death in adults with COVID-19

Abstract: Background Diabetes is associated with poor coronavirus disease 2019 (COVID-19) outcomes. However, little is known on the impact of undiagnosed diabetes in the COVID-19 population. We investigated whether diabetes, particularly undiagnosed diabetes, was associated with an increased risk of death from COVID-19. Methods This retrospective study identified adult patients with COVID-19 admitted to Tongji Hospital (Wuhan) from January 28 to April 4, 202… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 44 publications
4
25
0
3
Order By: Relevance
“…Diabetes in our cohort was present in 32% of the patients, which is in line with a large cohort of 5700 COVID-19 patients from the USA with 34% [55]. This comorbidity is associated with a higher mortality rate [56,57]. This fact was also proven in another meta-analysis performed by Huang and colleagues [53], which showed that diabetes is associated with severe COVID-19 and developing ARDS.…”
Section: Correlation Of Dad With Clinical Parameterssupporting
confidence: 89%
“…Diabetes in our cohort was present in 32% of the patients, which is in line with a large cohort of 5700 COVID-19 patients from the USA with 34% [55]. This comorbidity is associated with a higher mortality rate [56,57]. This fact was also proven in another meta-analysis performed by Huang and colleagues [53], which showed that diabetes is associated with severe COVID-19 and developing ARDS.…”
Section: Correlation Of Dad With Clinical Parameterssupporting
confidence: 89%
“…Congruent with other recent studies, we found a high incidence of prediabetes (HbA1c 42–48 mmol/mol) or diabetes (HbA1c > 48 mmol/mol) in patients with severe Covid‐19. 12 , 13 , 14 In our study, prediabetes and undiagnosed diabetes as well as a poor glycemic control in patients with known diabetes mellitus constituted 74% of the patients with respiratory failure. In the same group of patients with respiratory failure, 62.5% of the patients were admitted to the ICU, of whom 61% were mechanically ventilated and 14% were supported with renal replacement therapy, indicating a severe course of the infection.…”
Section: Discussionmentioning
confidence: 53%
“…Diabetes, among other comorbidities, increases the risk of a serious adverse prognosis for people who contract Covid-19, as shown by numerous individual studies, meta-analyses and systematic reviews ( Figure 1 ). ( Zhang et al, 2020a ; Ciceri et al, 2020 ; Yu et al, 2020 ; Zhou et al, 2020 ; Barron et al, 2020 ; Abu-Jamous et al, 2021 ; Lee et al, 2020 ; Wu J. et al, 2020 ; Fox et al, 2021 ; Chilimuri et al, 2020 ; Guan W. J. et al, 2020 ; Zhu et al, 2020 ; Yan et al, 2020 ; Petrilli et al, 2020 ; Al-Salameh et al, 2021 ; Shang et al, 2021 ; Xu et al, 2020 ; Kim et al, 2020 ; Liu et al, 2020 ; Docherty et al, 2020 ; Shi et al, 2020 ; Smith et al, 2020 ; Saha et al, 2021 ; Liu et al, 2021 ; Kaminska et al, 2021 ; Elezkurtaj et al, 2021 ; Corona et al, 2021 ; Sun et al, 2021 ; Bud et al, 2020 ; Palaiodimos et al, 2020 ; Miller et al, 2020 ; Varikasuvu et al, 2021 ; Hussain et al, 2020 ; Shang et al, 2020 ; Guo L. et al, 2020 ; Aggarwal et al, 2020 ; Zaki et al, 2020 ; Parveen et al, 2020 ; Wu et al, 2021 ; Mantovani et al, 2020 ; Huang I. et al, 2020 ; Kumar et al, 2020 ; Roncon et al, 2020 ) Populations of patents hospitalised or entering intensive care for Covid-19 include a relatively high prevalence of diabetes, typically 1.5-3 fold greater than similar populations without diabetes ( Carey et al, 2018 ; Abdi et al, 2020 ; Apicella et al, 2020 ; Bhatti et al, 2020 ; Wu C. et al, 2020 ; Hussain et al, 2020 ; Sathish and Cao, 2021 ;…”
Section: Diabetes and Covid-19 Outcomesmentioning
confidence: 99%
“…Diabetes, among other comorbidities, increases the risk of a serious adverse prognosis for people who contract Covid-19, as shown by numerous individual studies, meta-analyses and systematic reviews (Figure 1). (Zhang et al, 2020a;Ciceri et al, 2020;Yu et al, 2020;Zhou et al, 2020;Barron et al, 2020;Abu-Jamous et al, 2021;Lee et al, 2020;Fox et al, 2021;Chilimuri et al, 2020;Guan W. J. et al, 2020;Zhu et al, 2020;Yan et al, 2020;Petrilli et al, 2020;Al-Salameh et al, 2021;Shang et al, 2021;Xu et al, 2020;Kim et al, 2020;Liu et al, 2020;Docherty et al, 2020;Shi et al, 2020;Smith et al, 2020;Saha et al, 2021;Liu et al, 2021;Kaminska et al, 2021;Elezkurtaj et al, 2021;Corona et al, 2021;Sun et al, 2021;Bud et al, 2020;Palaiodimos et al, 2020;Miller et al, 2020;Varikasuvu et al, 2021;Hussain et al, 2020;Shang et al, 2020;Guo L. et al, 2020;Aggarwal et al, 2020;Zaki et al, 2020;Parveen et al, 2020;Wu et al, 2021;Mantovani et al, 2020;…”
Section: Diabetes and Covid-19 Outcomes Prognosis In Patients With Co...mentioning
confidence: 99%